1986
DOI: 10.1038/clpt.1986.161
|View full text |Cite
|
Sign up to set email alerts
|

Dose effects of alfentanil in human analgesia

Abstract: Alfentanil, a rapidly acting opioid, was given in subanesthetic doses to 10 subjects in a laboratory setting. Analgesia was assessed from the subjects' responses to painful dental stimulation. A subjective pain report (PR) and brain evoked potential (EP) amplitude were obtained repeatedly before and after injection on each of 4 testing days, on which the following intravenous doses were administered: 0 (saline solution), 5, 10, and 15 micrograms/kg. Significant dose effects were observed for EP amplitude durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results of the present study support the hypothesis The analgesic effects of alfentanil in awake subjects are dose-related (Hill et al 1986). The mean minimum effec- tive analgesic plasma concentration in the eady postoperative period has been reported to range from approximately 35 ng ml-r to 56 ng ml-r. (Persson et al 1988 were significantly lower than in group 2, suggesting a dose-dependent effect.…”
Section: Discussionsupporting
confidence: 80%
“…The results of the present study support the hypothesis The analgesic effects of alfentanil in awake subjects are dose-related (Hill et al 1986). The mean minimum effec- tive analgesic plasma concentration in the eady postoperative period has been reported to range from approximately 35 ng ml-r to 56 ng ml-r. (Persson et al 1988 were significantly lower than in group 2, suggesting a dose-dependent effect.…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have shown that potentials, evoked by noxious laser stimuli, correlate with perceived pain intensity [10,11,14,15]. In contrast, there is a lack of correlation between the amplitude of the vertex potential evoked by nociceptive electrical stimulation on the surface of the skin and subjective pain rating [16,17]. This suggests that transcutaneous electrically evoked vertex potentials are not a reliable measure or correlate for changes within the nociceptive system.…”
Section: Discussionmentioning
confidence: 41%
“…There was a reduction in the peak-to-peak amplitudes for the evoked vertex potentials elicited by nociceptive electrical and laser stimulation at the two higher isoflurane concentrations (see table 2), which could be interpreted as an analgesic effect [16,[20][21][22]. But the same decrease in the peak-to-peak amplitudes was observed also for the non-nociceptive AEP, and furthermore the perceived pain intensity did not differ significantly from baseline.…”
Section: Discussionmentioning
confidence: 56%
“…The optimal Ce for alfentanil should provide maximum pain relief with minimum side-effects. Alfentanil's analgesic effects are dose related 16 and vary between 40 ng/ml 10,17 and 110 ng/ml 8 for effective postoperative analgesia. Pavlin et al 10 found that combining propofol and alfentanil could produce sedation and analgesia that was greater than that observed with either drug alone.…”
Section: Resultsmentioning
confidence: 99%